Strategi adaptasi teknologi artefak litik Toalean di Situs Leang Jarie dan Cappalombo 1, Sulawesi Selatan - nfn. Suryatman; nfn. Fakhri; Budianto Hakim; nfn. Hasanuddin; Muhammad Nur; Khadijah Thahir Muda; nfn. Isbahuddin; Afdalah Harris; Khairun Anshari (Balai Arkeologi Yogyakarta, 2022)
The intensified research on Toalean lithic artifacts is still lacking in comparative study of stone tool technology, which is necessary to inquire into the adaptation of different tool-making technology due to environmental factors. This paper discusses a comparative study of Toalean lithic artefacts from Leang Jarie in the Maros-Pangkep lowlands and Cappalombo 1 in the Bontocani highlands by the classification and analysis of lithic artifacts, as well as surveys and observations of raw material sources around the site. The results show an adaptation strategy to the availability of raw materials, resulted in a different trend on both sites. The low quality of chert in Bontocani has prompted stone tool manufacture in Cappalombo 1 to use various raw material and to apply bipolar techniques more frequently in reduce and retouch of the flakes. On the other hand, raw material utilization of chert in Leang Jarie is more homogenous and direct percussion technique is more frequently used.